The Iranian position on the Russian-Ukrainian war in 2022 - Abdallah, Noura Ali (Journal of Economic, Administrative and Legal Sciences, 2023)
The study dealt with the Iranian position regarding the Russian-Ukrainian war, as its position was a reflection of its foreign policy, and a continuation of the approach it has followed since the days of the Islamic Revolution in 1979, due to the nature of its international and regional relations on the one hand, and its desire to preserve its interests in the negotiations of the nuclear agreement between the 4+1 countries and the USA indirectly.The study worked to identify indicators of the escalation of the Ukrainian crisis in 2014, which led to its war with Russia on February 24, 2022, as Tehran condemned the main causes of the war represented in the expansion of NATO to the East, and its repercussions on the regional and international levels.The study found an explanation of Iran's balanced position between the United States of America and Russia; Tehran has balanced its relationship with Russia and Western countries on the one hand, and was keen not to clash with the United States of America on the other, with a desire to find a solution regarding the nuclear deal negotiations that are still frozen, and to achieve mutual dependence and economic cooperation with Russia, which seeks to prove itself in the new world system.
Keywords: Iran; Russia; the United States of America; NATO; the nuclear agreement; Security guarantees